Mobility and delay in greedy geographic routing. (1st January 2012) - Cadger, Fraser; Curran, Kevin; Santos, Jose A.; Moffett, Sandra
Opportunistic networking and geographic routing both represent fields of research in the area of mobile ad-hoc networking that seek to create dynamic, hop-by-hop, localised paths from source to destination thus enabling connectivity where no end-to-end path may be possible. Where they differ is in their approach to the problem of providing connectivity in a changing network. While geographic routing makes decisions based on physical locations, opportunistic networking seeks to take advantage of node mobility and select nodes that will physically carry the message closer to the destination and reduce the overall hop count. In spite of their differences, the similarity of the two approaches presents the opportunity of combining aspects from both paradigms to create hybrid protocols. This paper attempts to analyse the relationship between mobility and delay in greedy routing for use in designing future QoS-aware hybrid opportunistic-geographic protocols.